Popularizing underutilized arid fruits for nutrition - Krishna, Hare; Singh, R S; Singh, D; Saroj, P L (Indian Horticulture, 2019)
Arid region is characterized by stressful edaphic and environmental conditions like tenuous moisture regime, intense solar radiation and extreme temperature. Under such distressing conditions, cultivation of field crops or other commercial fruit crops is a unprofitable venture. However, underutilized fruit crops such as lasoda, ker, pilu, phalsa, jharber, bordi, karonda, sehtoot, bael etc. can be grown successfully with minimum agricultural inputs in arid region. Further, these fruits are seldom affected seriously by diseases and pests due to their hardy nature. These fruits are rich source of vitamins, minerals and phytochemicals; besides possessing medicinal properties. These underutilized fruits have the immense potential of transforming the economy of rural and tribal areas provided they are given much needed attention through health campaigns about their nutritional importance.